Discovery of novel antitumor nitric oxide-donating b-elemene hybrids through inhibiting the PI3K/Akt pathway - Chen, Jichao; Wang, Tianyu; Xu, Shengtao; Zhang, Pengfei; Lin, Aijun; Wu, Liang; Yao, Hequan; Xie, Weijia; Zhu, Zheying; Xu, Jinyi (Elsevier, 2017)
A series of novel furoxan-based NO-donating b-elemene hybrids were designed and synthesized to improve the anticancer efficacy of natural b-elemene. The bioassay results indicated that all of the target compounds exhibited significantly improved antiproliferative activities against three cancer cell lines (SGC-7901, HeLa and U87) compared to parent compound b-elemene. Interestingly, these compounds displayed excellent sensitivity to U87 cells with IC50 values ranging from 173 to 2 nM. Moreover, most compounds produced high levels of NO in vitro, and the antitumor activity of 11a in U87 cells was markedly attenuated by an NO scavenger (hemoglobin or carboxy-PTIO). Further mechanism studies revealed that 11a caused the G2 phase arrest of the cell cycle and induced apoptosis of U87 cells by preventing the activation of the PI3K/Akt pathway. Moreover, 11a significantly suppressed the tumor growth in H22 liver cancer xenograft mouse model with a tumor inhibitory ratio (TIR) of 64.8%, which was superior to that of b-elemene (TIR, 49.6%) at the same dose of 60 mg/kg. Together, the remarkable biological profiles of these novel NO-donating b-elemene derivatives may make them promising candidates for the intervention of human cancers.